2022
DOI: 10.1186/s12904-022-01071-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review defining non-beneficial and inappropriate end-of-life treatment in patients with non-cancer diagnoses: theoretical development for multi-stakeholder intervention design in acute care settings

Abstract: Background Non-beneficial treatment is closely tied to inappropriate treatment at the end-of-life. Understanding the interplay between how and why these situations arise in acute care settings according to the various stakeholders is pivotal to informing decision-making and best practice at end-of-life. Aim To define and understand determinants of  non-beneficial and inappropriate treatments for patients with a non-cancer diagnosis, in acute care s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Caregivers should also be involved in the decision-making process to help clarify the patients’ wishes as legitimate surrogates. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Caregivers should also be involved in the decision-making process to help clarify the patients’ wishes as legitimate surrogates. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Impaired decision-making and the lack of prognostic awareness for patients, and provider ambiguity and prognostic uncertainty contribute, as does a lack of consideration for resource utilization. [38] In transplantation, the latter factors in heavily. Studies on intensive care unit patients at the end of life showed that gravely ill patients wanted to know the full truth relating to their disease and wanted respect for dignity, rather than experience unnecessary and distressing symptoms.…”
Section: What Outcomes Are We Truly Measuring?mentioning
confidence: 99%
“…A recent systematic review defining “nonbeneficial” and “inappropriate end-of-life care” for gravely ill, noncancer patient care attempted to address multistakeholder perceptions and roles in performing futile care. Impaired decision-making and the lack of prognostic awareness for patients, and provider ambiguity and prognostic uncertainty contribute, as does a lack of consideration for resource utilization 38 . In transplantation, the latter factors in heavily.…”
Section: What Outcomes Are We Truly Measuring?mentioning
confidence: 99%
“…Despite establishment of a formal definition, fulfillment of the criteria for potentially inappropriate is a matter of perception , and thus like non-beneficial treatment, it includes a subjective values-based judgement ( 3 ). The terms, potentially inappropriate treatment and non-beneficial are not synonymous ( 4 ). Nonbeneficial treatment emphasizes the lack of expected benefit and the imbalance between the burdens and expected benefits while potentially inappropriate treatment acknowledges that perceptions of appropriateness or benefit are influenced by the preferences, culture and values of patients and providers ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The terms, potentially inappropriate treatment and non-beneficial are not synonymous ( 4 ). Nonbeneficial treatment emphasizes the lack of expected benefit and the imbalance between the burdens and expected benefits while potentially inappropriate treatment acknowledges that perceptions of appropriateness or benefit are influenced by the preferences, culture and values of patients and providers ( 4 ). What constitutes potentially inappropriate is open to interpretation and the associated subjectivity and ambiguity thus prevent objective measurement of potentially inappropriate treatment.…”
Section: Introductionmentioning
confidence: 99%